RNF4 interacts with both SUMO and nucleosomes to promote the DNA damage response. (8th April 2014) - Groocock, Lynda M; Nie, Minghua; Prudden, John; Moiani, Davide; Wang, Tao; Cheltsov, Anton; Rambo, Robert P; Arvai, Andrew S; Hitomi, Chiharu; Tainer, John A; Luger, Karolin; Perry, J Jefferson P; et al.
Synopsis <boxed-text content-type="graphic" id="embr201338369-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> RNF4 is an important ubiquitin ligase in the DNA damage response (DDR) that targets SUMOylated proteins. This study shows that it also contains a nucleosome‐targeting motif that crucially supports the DDR genome‐wide. RNF4 promotes ATM‐dependent 53BP1 recruitment and repair at dysfunctional telomeres. RNF4 RING domain contains an RNF168 and RING1b‐related nucleosome‐targeting motif. RNF4 recognizes both SUMO and nucleosomes to support DNA repair .